2019
DOI: 10.1002/cam4.2350
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long noncoding RNA NORAD is upregulated in epithelial ovarian cancer and its downregulation suppressed cancer cell functions by competing with miR‐155‐5p

Abstract: Purpose In the present study, we evaluated the expression and function of human long noncoding RNA (lncRNA) activated by DNA damage (NORAD) in human epithelial ovarian cancer (EOC). Methods NORAD expression was evaluated by qRT‐PCR in EOC cell lines and in situ EOC clinical samples. Lentivirus‐mediated NORAD downregulation was conducted in OVCAR‐3 and ES‐2 cells, and its effect on cancer cell proliferation, bufalin chemoresistance, cell‐cycle transition in vitro, and xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…LncRNAs regulate biological behaviors including cell proliferation, cell apoptosis, cell metastasis etc., during tumorigenesis [11][12][13]. For instance, lncRNA NORAD promoted cell proliferation by competitively binding with miR-155-5p [14]. LINC00339 accelerated cell metastasis in pancreatic cancer by sponging miR-497-5p and modulating IGF1R [15].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs regulate biological behaviors including cell proliferation, cell apoptosis, cell metastasis etc., during tumorigenesis [11][12][13]. For instance, lncRNA NORAD promoted cell proliferation by competitively binding with miR-155-5p [14]. LINC00339 accelerated cell metastasis in pancreatic cancer by sponging miR-497-5p and modulating IGF1R [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that lncRNAs participate in multiple cancers and regulate the chemoresistance of cancer cells, including NSCLC (Nagasaka et al 2018). NORAD has been discovered to be a tumour promoter in several cancers (Tao et al 2019;Tong et al 2019), but little is known whether NORAD can affect the drug resistance of NSCLC cells. In the present study, we investigated the role of NORAD in drug resistance of A549/DDP cells and its potential mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the involvement of miRNAs in tumorigenesis and their signi cance as effective biomarkers are also becoming increasingly appreciated [14]. miR-155-5p has been found to regulate the development of various cancer types, including human epithelial ovarian cancer [16], cervical cancer [17,18], and colon cancer [19]. It has been reported that some certain long non-coding RNAs (lncRNAs) suppress HCC development by sponging miR-155-5p [20]; miR-155-5p modulated the malignancy of HCC by regulating Wnt/β-catenin signaling or suppressing PTEN through the PI3K/Akt pathway [21,22]; therefore, miR-155-5p can be a promising therapeutic target for HCC patients.…”
Section: Discussionmentioning
confidence: 99%